0415 Associations Between Pain, Depression, Stress, and Substance Use in Nurses With and Without Insomnia. (12th April 2019) - Kumar, Riya A; Slavish, Danica C; Messman, Brett; Wardle, Sophie; Dietch, Jessica R; Ruggero, Camilo J; Kelly, Kimberly; Taylor, Daniel J
Abstract: Introduction: Insomnia and pain have been shown to increase risk for development of depression and substance use disorders. Depression, substance use, stress, and pain are also strongly correlated with sleep impairment. No studies have examined associations between insomnia, pain, stress, substance use, and depression in a sample of nurses, who may experience these disturbances due to stressful work environments, intense physical demands, and rotating work schedules. Therefore, the present study examined if insomnia symptoms, pain symptoms, and perceived stress were associated with alcohol use and depressive symptoms in nurses, and if insomnia diagnosis moderated these associations. Methods: Participants were 400 nurses (92% female; 78% white, mean age = 39.51 ± 11.13) recruited from two hospitals for a parent study, "Sleep and Vaccine Response in Nurses (SAV-RN)" (R01AI128359-01, PIs: Taylor & Kelly). Participants completed measures of depression, pain, insomnia, and stress. Linear regression was used to assess the associations between insomnia symptoms, stress, and pain with depressive symptoms and substance use. Insomnia diagnosis (based on diagnostic cutoffs from questionnaire data) was examined as a moderator of the associations between pain, stress, depressive symptoms, and substance use. Results: Greater insomnia symptoms were associated with consuming fewer drinks per week ( p = .04), and greater perceived stress was associated with consuming more drinks per week ( p = .01). Greater insomnia symptoms, perceived stress, and pain were each associated with greater depressive symptoms ( p s < .001). Insomnia diagnosis moderated the association between perceived stress and depressive symptoms (β = 0.11, p = .05), such that nurses with insomnia disorder had a stronger positive relationship between perceived stress and depressive symptoms. Conclusion: Results suggest insomnia symptoms, stress, and pain were associated with greater mood disturbance. Greater stress was associated with greater substance use, which may reflect coping attempts. Nurses with insomnia may be particularly susceptible to increases in depressive symptoms under times of stress. Given that nurses are the first-line of care in hospital settings, it is essential to address these problems proactively and comprehensively. Support (If Any): NIAID R01AI128359-01